Z property for the shuffling calculus. (10th August 2022) - Nakazawa, Koji; Fujita, Ken-etsu; Imagawa, Yuta
ABSTRACT: This paper gives a new proof of confluence for Carraro and Guerrieri's call-by-value lambda calculus λ v σ with permutation rules. We adapt the compositional Z theorem to λ v σ .